2016
DOI: 10.1016/j.jval.2015.09.2938
|View full text |Cite
|
Sign up to set email alerts
|

The “Efficacy-Effectiveness Gap”: Historical Background and Current Conceptualization

Abstract: The third paradigm provides an opportunity to look beyond any dichotomy between "standardized" versus "real-life" characteristics of the health care system and study designs. Namely, future research will determine whether the identification of these contextual factors can help to best design randomized controlled trials that provide better estimates of drugs' effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 53 publications
1
97
0
5
Order By: Relevance
“…Approved since 2006 in the United States to treat myelodysplastic syndrome and since 2012 in the European Union with an indication for treatment of adult AML patients who are not candidates for standard induction chemotherapy, it showed improved response rates as compared with standard available therapies and no major safety issues in clinical trials conducted in elderly AML patients . Real‐world (RW) studies are needed to confirm and support clinical studies results in unselected and heterogenous populations of routinely treated patients, in order to translate clinical trials into clinical practice (so called efficacy‐effectiveness gap) . Despite widespread use of decitabine to treat AML, RW data based on the registered treatment schedule (20 mg/m 2 daily for 5 days) are very scanty .…”
Section: Introductionmentioning
confidence: 99%
“…Approved since 2006 in the United States to treat myelodysplastic syndrome and since 2012 in the European Union with an indication for treatment of adult AML patients who are not candidates for standard induction chemotherapy, it showed improved response rates as compared with standard available therapies and no major safety issues in clinical trials conducted in elderly AML patients . Real‐world (RW) studies are needed to confirm and support clinical studies results in unselected and heterogenous populations of routinely treated patients, in order to translate clinical trials into clinical practice (so called efficacy‐effectiveness gap) . Despite widespread use of decitabine to treat AML, RW data based on the registered treatment schedule (20 mg/m 2 daily for 5 days) are very scanty .…”
Section: Introductionmentioning
confidence: 99%
“…The focus on HRs from clinical trials is further complicated by the 'efficacy-effectiveness gap', the commonly observed discrepancy between clinical trial results and the performance of a treatment in real-world practice [10]. For welldocumented reasons -including healthcare system characteristics, clinical trial measurement methods and complex interactions between a drug's biological effect and contextual factors -clinical trials do not always predict realworld outcomes [11]. Results obtained in formal trials can over-or underestimate real-world effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy trials determine whether an intervention produces the expected result under ideal circumstances. Effectiveness trials measure the degree of beneficial effect under real world clinical settings . For these lifestyle modifications in hypertension, efficacy has been well established, but effectiveness less so.…”
Section: Efficacy Vs Effectivenessmentioning
confidence: 99%
“…Similarly, for exercise, the interventions are of a supervised exercise program and not an exhortation to “do more exercise.” Last, the data on alcohol reduction is also based on successful reduction with intensive counseling and follow up. All of the 3 aspects in the first paradigm of the efficacy to effectiveness gap apply here: physician behavior, attention to adherence, and disparity in access to resources and care . Clearly interventions as described above are thus not feasible to be translated into routine clinical practice yet, and hence, it is unreasonable to expect a remarkable behavior change from mere counselling.…”
Section: Efficacy Vs Effectivenessmentioning
confidence: 99%